Tinjauan Penerapan Material Akustik untuk Mengontrol Gangguan Akustik pada Kamar Tipe Monument View di Hotel Mandarin Oriental Jakarta - Astono, Natasha Putri; Kusnaedi, Iyus (Waca Cipta Ruang, 2024)
Mandarin Oriental Hotel Jakarta is a five-star hotel located in the center of Jakarta. The atmosphere of a hotel room plays an important role in creating quality rest. Acoustic systems and room noise control in an architectural context are the key to creating comfort. This research aims to examine the application of acoustic materials in rooms at the Mandarin Oriental Hotel Jakarta. Based on survey results obtained from visitor reviews on the website and direct surveys, the Mandarin Oriental Jakarta hotel room area has problems related to noise pollution or light pollution originating from noise on the highway. In this research, the method employed is a qualitative, utilizing an identification approach. With a focus for the application of soundproofing systems, this research seeks solutions to improve acoustic comfort within the hotel rooms in question, using multiple data sources to provide some insight into the problem at hand. In this regard, clear results have been acquired to enhance the quality of acoustic comfort in hotel rooms, by using certain material specifications. Based on research findings, understanding and how best to apply soundproofing techniques can help reduce sound pollution entering hotel rooms.